Pelaksanaan Kegiatan Ekstrakurikuler Band di MAN 2 Kota Padang dengan Pendekatan Literasi Plus Media - Zura, Habib Aulia; Wimbrayardi, Wimbrayardi (Al-DYAS, 2024)
This study aims to describe the implementation of band extracurricular activities at MAN 2 Padang City. This type of research is qualitative research with descriptive methods. Data collection techniques were carried out by observation, interviews, literature study, and documentation. The data in this study used secondary data. The steps of analyzing data are collecting, describing and concluding data. Band extracurricular activities at MAN 2 Padang City with a literacy plus media approach are carried out with 3 stages, namely planning, implementation, and evaluation. band extracurricular activities at MAN 2 Padang City have become one of the extracurricular activities that can develop students' musical abilities. The planning process, practice, and strong support from coaches and coaches have contributed to the success of this extracurricular band. For the students involved, this extracurricular band has provided a lot of knowledge and experience in developing musical abilities and art activities and has provided inspiration to develop their musical abilities further.